Komunikasi Budaya dalam Seni Pertunjukan Ogoh-Ogoh Hindu Bali di Tengah Transpormasi Media - Kadek Arya Juniati; I Wayan Astraguna (MUKASI: Jurnal Ilmu Komunikasi, 2025)
Balinese art has its own peculiarities that are very attached to religious nuances. Its values are reflected in three main elements: satyam (truth, honesty), sivam (purity), and sundaram (beauty). As an integral part of Hindu culture, performing arts in Bali are not only a form of entertainment, but also a medium to convey religious teachings, mythology, and social and cultural values that are passed down through generations. In this case, cultural communication has a crucial role in building understanding, appreciation, and tolerance between cultural groups. This study uses a descriptive qualitative method to examine how digital media transformation affects the form, presentation, and meaning of Ogoh-ogoh performing arts. Data was obtained through digital observation of @infotampaksiring Instagram accounts and analyzed interpretively with a theoretical approach to cultural communication and digital media. Ogoh-ogoh symbolizes bhuta kala, a symbol of negative energy that needs to be neutralized ahead of Nyepi Day. The emergence of social media such as Instagram and TikTok has changed the way people present and interpret this tradition. Although it presents opportunities for cultural preservation, a contextual narrative is needed so that the spiritual and philosophical values of Ogoh-ogoh are maintained in the midst of the rapid flow of digitalization.